Corporate Divestitures and Spinoffs in Singapore - KOH, Francis (Institutional Knowledge at Singapore Management University, 2005)
This paper discusses the different forms of corporate divestitures, the motives for this corporate activity, and the empirical findings about their economic outcomes. A sample of corporate divestitures is also used to identify the main motivations in the Singapore context. We conclude that divestitures are carried out to achieve operational efficiency and gain incremental profitability and liquidity. Using share price data around the event-dates, we show that announcements of divestitures generally lead to significant increases in the returns of the parent company. The positive abnormal returns are related to the relative size of the divestitures and the computed accounting gains. Overall, corporate divestiture is a value-increasing activity for Singapore companies.